Purification and characterization of enterovirus 71 viral particles produced from vero cells grown in a serum-free microcarrier bioreactor system. - Chia-Chyi Liu (PLoS ONE, 2011)
BACKGROUND: Enterovirus 71 (EV71) infections manifest most commonly as a childhood exanthema known as hand-foot-and-mouth disease (HFMD) and can cause neurological disease during acute infection. PRINCIPAL FINDING: In this study, we describe the production, purification and characterization of EV71 virus produced from Vero cells grown in a five-liter serum-free bioreactor system containing 5 g/L Cytodex 1 microcarrier. The viral titer was >10(6) TCID(50)/mL by 6 days post infection when a MOI of 10(-5) was used at the initial infection. Two EV71 virus fractions were separated and detected when the harvested EV71 virus concentrate was purified by sucrose gradient zonal ultracentrifugation. The EV71 viral particles detected in the 24-28% sucrose fractions had an icosahedral structure 30-31 nm in diameter and had low viral infectivity and RNA content. Three major viral proteins (VP0, VP1 and VP3) were observed by SDS-PAGE. The EV71 viral particles detected in the fractions containing 35-38% sucrose were 33-35 nm in size, had high viral infectivity and RNA content, and were composed of four viral proteins (VP1, VP2, VP3 and VP4), as shown by SDS-PAGE analyses. The two virus fractions were formalin-inactivated and induced high virus neutralizing antibody responses in mouse immunogenicity studies. Both mouse antisera recognized the immunodominant linear neutralization epitope of VP1 (residues 211-225). CONCLUSION: These results provide important information for cell-based EV71 vaccine development, particularly for the preparation of working standards for viral antigen quantification.